Faktor Yang Mempengaruhi Penerapan Pasal 1367 Kuhperdata Terhadap Pelaku Usaha Laundry Di Kabupaten Gorontalo - Andi Fahrul Adhzulhaq; Nirwan Junus; Mohammad Taufiq Z. Sarson (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to find out what factors influence the application of Article 1367 of the Civil Code to laundry business actors in Gorontalo Regency. The research method used is empirical which uses field data to understand, solve and anticipate existing problems. The results of the research show that the factors influencing the application of Article 1367 of the Civil Code by laundry business actors in Gorontalo Regency are, business actors and consumers do not understand the rights and obligations specified in statutory regulations; Business actors do not have good intentions; and business actors do not want to lose.